Percutaneous Endoscopic Gastrostomy Tube Placement in COVID-19 Patients - Goyal, Hemant; Ali, Aman; Bansal, Pardeep (Frontiers in Nutrition, 2021)
Intensive care units (ICU) around the world are overburdened with COVID-19 patients with ventilator-dependent chronic respiratory failure (VDRF). Gastroenterology evaluations are being made to address the provision of chronic enteral feeding with the help of percutaneous endoscopic gastrostomy (PEG) placements in these patients. The placement of the PEG tube along with tracheostomy in patients with COVID-19 and prolonged VDRF may expedite discharge planning and increase the availability of ICU beds for other patients. Herein, we describe a multidisciplinary approach of PEG tube placements for patients with SARS-CoV-2-induced chronic VDRF for continued enteral feeding to avoid complications and decrease the length of stay.